A crônica como estratégia de ensino na formação leitora dos alunos do 1º ano do ensino médio, na escola prof. Bernardino Pereira de Barros - GOMES, Nilzete Moraes (2023)
This paper discussed the strategies for education and training of readers, and therefore producers from the genre Chronicle as subsidy for this training. However, the work deteu mainly on analyzing the chronicles produced by the students of 1st year high school State School of Elementary and Secondary Education Prof. Bernardino Pereira de Barros using an evaluative model that propose a better rectification gradual process of teaching and learning. It is worth mentioning that this study is part of the theoretical perspective discussed by PCNs, Luiz Antônio Marcuschi, Bakhtin, Bronckart, Antônio Cândido, Isabel Solé, and others who helped me in this research and will be cited as a reference in this work. The methodological choice has a basic qualitative and interpretative, which, in view of the involvement in the classroom and its participants endorse the concern of the research described in this locus from your own environment, observing and analyzing the cultural traits of group. Such analysis objects received treatment methodology based on ethnographic perspective, which considers the natural locus of action of informants - in this case, the classroom - and also the analysis of textual production collected - which, for this study, was used in the analysis of texts produced by the students. We emphasize that the body of data presented was chosen due to present substantial difference between prescribed work and real work.